Improvement of Strength Characteristics of a Highly Plastic Expansive Soil with Fly Ash - Gaye Kodaz; Hasan Fırat Pulat; Hasan Emre Demirci (Sakarya Üniversitesi Fen Bilimleri Enstitüsü Dergisi)
Highly plastic expansive clays swell or shrink due to change in moisture content and they often have very low bearing capacity. Construction of engineering structures particularly pavements and lightweight buildings on problematic soils such as highly plastic expansive clays may create severe structural problems due to poor engineering properties of that kind of soil. This study focused on the influence of fly ash on strength properties of highly expansive clays which are problematic soils due to their undesirable engineering characteristics such as high plasticity index, liquid limit, swelling and shrinkage characteristics, and low bearing capacity. Atterberg’s limit tests and hydrometer tests were conducted to obtain consistency limits and grain-size distribution of the highly plastic expansive clay. Standard proctor tests for clay samples with different fly ash contents such as 10%, 15%, and 20% were performed to determine maximum dry densities and optimum water contents of the mixtures of clay and fly ash. The clay and fly ash mixtures were prepared at optimum water content and maximum dry density for unconfined compression strength (UCS) and California Bearing Ratio (CBR) tests. Effects of fly0ash content on the strength characteristics of a highly plastic expansive clay were investigated through unconfined compression and CBR tests. The experiment results showed that fly0ash is a promising additive to enhance strength characteristics of highly plastic expansive clays. An approximately 66% increase in UCS and CBR values was observed with the addition of 20% fly ash into the clay mixture in weight.